IMPROVING FINANCIAL PROCESSES IN SCHOOL EDUCATIONAL ORGANIZATIONS THROUGH INFORMATION SYSTEMS (American Journal of Business Management, Economics and Banking, 2024)
This article discusses the problems of evaluating the quality of educational activities in preschool educational institutions and methodological approaches to evaluating the effectiveness of budget expenditures on education based on the analysis available in world practice.